Exploring the impact of restaurant taxpayer behavior on the success of tapping box technology in Yogyakarta - Alfurqan, Muhammad; Urumsah, Dekar (Journal of Accounting and Investment, 2025)
Research aims: This study aims to analyze the influence of taxpayer compliance, awareness, and knowledge on the success of tapping box technology. Additionally, the study considers the role of gender as a moderating .Design/Methodology/Approach: This research used a quantitative approach by employing a non-probability sampling method with a census technique involving all 194 restaurant taxpayers in Yogyakarta City equipped with tapping box technology. The data were analyzed using the SEM-PLS method and Multi-Group Analysis.Research findings: The results of the study indicate that taxpayer compliance and knowledge have a significant impact on the success of tapping box technology. However, taxpayer awareness does not have a significant impact on the success of tapping box technology. In comparison, gender does not have a significant role in the success of tapping box technology.Theoretical contribution/Originality: This research contributes to the development of taxation literature, particularly in regional taxes, by highlighting the role of taxpayer compliance and knowledge in the success of taxation technology. These findings offer a new perspective that can enrich the literature in the field of regional taxation.Practitioner/Policy implication: These findings imply that the Yogyakarta City Government should prioritize improving taxpayer compliance and knowledge as the primary strategy to achieve greater success in tapping box technologyResearch limitation/Implication: Although the sample represents over 69% of the population, the research has limitations, primarily due to 31% of the population declining to complete the questionnaire without offering a clear explanation.